In vitro and in vivo studies of the antidiabetic potential of Red Sea sponge-associated fungus “Aspergillus unguis” isolate SP51-EGY with correlations to its chemical composition - Mona E. Aboutabl, Yousreya. A. Maklad, Mohamed S. Abdel-Aziz, Faten K. Abd El-Hady (Journal of Applied Pharmaceutical Science, 2022)
Diabetes mellitus is one of the most prevalent chronic diseases. The main objective is to determine ‎antidiabetic and antioxidant activities of Red Sea sponge-associated fungus “Aspergillus ‎unguis” isolate SP51-EGY secondary metabolites with concomitant gas chromatography/mass spectrometry (GC/MS) analysis of active extracts.‎ In vitro α-glucosidase inhibition and antioxidant capacity were determined. In vivo, LD50 was determined in mice. Streptozotocin-induced diabetic mice were treated with mycelial-free culture filtrate and mycelial extracts. Serum blood glucose, serum C-peptide, glucagon-like peptide-1 (GLP-1), α-glucosidase, and adiponectin levels were estimated. Shake (Sh) filtrate and mycelial extracts demonstrated the highest significant in vitro α-glucosidase inhibitory activity. Sh mycelia demonstrated higher antioxidant capacity compared to Sh filtrate. In vivo, treatment with Sh mycelia (50 and 100 mg/kg) significantly lowered the blood glucose level by 27% and 54%, respectively, while Sh filtrate (125 and 250 mg/kg) significantly decreased the blood glucose level by 49% and 70%, respectively, compared to the diabetic group, respectively. Filtrate and mycelial extracts significantly increased C-peptide, GLP-1, and adiponectin, while significantly inhibiting α-glucosidase serum level compared to the diabetic group. GC/MS analysis revealed a high percentage of isovanillic acid; d-friedoolean-14-en-3-one; isochromanone derivative in filtrate extract; and palmitic, linolenic acids, and their esters in the mycelial extract. Therefore, secondary metabolites could be considered an effective strategy in the regulation of blood glucose level.
Keywords: Red Sea sponge-associated fungus, Aspergillus unguis SP51-EGY, antidiabetic, &alpha; -glucosidase inhibition, antioxidant, GC/MS analysis